Insoluble chitosan complex as a potential adsorbent for aflatoxin B1 in poultry feed - Delgado-Cedeño, Armando; Hernández-Martínez, Sara Paola; Ramos-Zayas, Yareellys; Marroquín-Cardona, Alicia Guadalupe; Méndez-Zamora, Gerardo; Franco-Molina, Moisés Armides; Kawas, Jorge R. (Frontiers in Materials, 2022)
As a class of secondary metabolites or toxins produced by fungi, aflatoxins can poison humans and animals; among them, aflatoxin B1 (AFB1) is the most dangerous one owing to its carcinogenic and mutagenic properties that increase risks for hepatocellular carcinoma in humans; hence, adsorbents such as smectites are commonly included in poultry feed to mitigate their effects. In this study, chitosan was crosslinked with sodium dodecyl sulfate (SDS) to form an insoluble polymer complex that is stable at the relevant physiological pH levels. The characterization via Fourier transforms infrared spectroscopy revealed the interaction between the sulfate groups of the SDS and the amine group of chitosan (1,016 and 819 cm-1); this result was further confirmed by the X-ray diffraction patterns with a change in the crystalline structure of the chitosan-insoluble complex (2θ = 4.76°, 7°, and 22°). The morphology of the chitosan-insoluble complex obtained using a field emission scanning electron microscope (FE-SEM) revealed that particles were slightly porous. After characterization, the performance of the chemically modified polymer complex was evaluated as an adsorbent for AFB1 and compared with those of the unmodified chitosan, soluble chitosan complex, and commercial montmorillonite clay binder. In addition, the polymer complex was investigated as an adsorbent in an in vitro model for the poultry gastrointestinal system. Sequestration of AFB1 by a chemically modified polymer complex was 93.4%, equivalent to that of commercial montmorillonite clay (99.5%). However, these treatments also sequestered microminerals, particularly selenium and iron. This pH-stable, high-capacity adsorbent could be used in poultry feed to reduce the uptake of AFB1.